ANALISIS PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2009-2011) - Elisa Purwitasari; Aditya Septiani (Diponegoro Journal of Accounting, 2013)
This study aims to analyze and provide empirical evidence of the influence of capital structure towards profitability. The analysis used independent variable of capital structure. The independent variable proxied with Short-term Debt to asset (STD), Long-term Debt to asset (LTD), and Total Debt to asset (TDA). The dependent variable is profitability. Return on Equity (ROE) is used to measured profitability. The sample used in this research was the secondary data from annual report of Manufacturing companies which listed on Bursa Efek Indonesia in 2009-2011. The sample was taken using the method of purposive sampling, and those meeting the selection criteria were also taken. The sample used was of 245 companies. The statistic method used was multiplied analysis linear regression with hypothesis testing of statistic t and F test. The results of research show that variables LTD does not have a significant relationship to profitability. While the STD and TDA variables have a negative relationship to profitability of manufacturing companies listed on Bursa Efek Indonesia over period 2009-2011.